Adjunctive Diquafosol Sodium 3% and Tear-Ferning Recovery After Pars Plana Vitrectomy: An Exploratory Randomized Trial - Ramzi Amin; Petty Purwanita; Rizka Yunanda (HM Publisher, 2026)
Background: Ocular-surface disturbance after pars plana vitrectomy (PPV) may impair tear-film stability and mucin-related function. Diquafosol sodium stimulates aqueous and mucin secretion through P2Y₂-receptor signaling, but evidence after PPV remains limited. Objective: This study evaluated adjunctive diquafosol sodium 3% using tear-ferning grade as an exploratory outcome. Methods: This single-center randomized trial enrolled 36 adults after PPV. Participants received diquafosol sodium 3% six times daily for eight weeks plus standard postoperative care (n=18) or standard care alone (n=18). Treatment was open label; tear-ferning assessment was performed by a masked assessor. Ferning grade was measured at postoperative weeks 1, 2, 4, and 8. Between-group comparisons used the Mann–Whitney U test with multiplicity adjustment, and standardized effect magnitudes were summarized using Hedges g with 95% confidence intervals. Results: Mean ferning grades were similar at week 1 (3.94±0.236 vs 3.72±0.461; p=0.203), week 2 (3.67±0.594 vs 3.72±0.461; p=0.938), and week 4 (2.89±0.323 vs 3.00±0.000; p=0.584). At week 8, the diquafosol group had a lower mean grade than the control group (2.11±0.471 vs 2.72±0.461; p=0.003), with a standardized effect magnitude of 1.28 (95% CI 0.57–1.99). No adverse events were reported. Conclusion: Adjunctive diquafosol was associated with better tear-ferning grade at eight weeks after PPV. The finding is exploratory and requires confirmation using larger, multicenter, placebo-controlled trials with multidimensional ocular-surface outcomes.